MECHANICAL PROCESSES IN BIOCHEMISTRY - Bustamante, Carlos; Chemla, Yann R; Forde, Nancy R; Izhaky, David (Annual review of biochemistry, 2004)
Mechanical processes are involved in nearly every facet of the cell cycle. Mechanical forces are generated in the cell during processes as diverse as chromosomal segregation, replication, transcription, translation, translocation of proteins across membranes, cell locomotion, and catalyzed protein and nucleic acid folding and unfolding, among others. Because force is a product of all these reactions, biochemists are beginning to directly apply external forces to these processes to alter the extent or even the fate of these reactions hoping to reveal their underlying molecular mechanisms. This review provides the conceptual framework to understand the role of mechanical force in biochemistry.